Macroeconomic Effects of Fiscal Adjustment: A Tale of two Approaches - Weonho Yang; Jan Fidrmuc; Sugata Ghosh (Center for Economic Studies and ifo Institute (CESifo), 2013)
We investigate the short-term effects of fiscal adjustment on economic activity in 20 OECD countries from 1970 to 2009. We compare two approaches: the traditional approach based on changes in cyclically adjusted primary balance (CAPB) and the narrative approach based on historical records. Proponents of the latter argue that it captures discretionary fiscal adjustment more accurately than the traditional approach. We propose a new definition of CAPB that takes account of fluctuations in asset prices and reflects idiosyncratic features of fiscal policy in individual countries. Using this new definition, we find that fiscal adjustments always have contractionary effects on economic activity in the short term; we find no evidence of expansionary (non-Keynesian) fiscal adjustments. Spending-based fiscal adjustments lead to smaller output loses than tax-based fiscal adjustment. These results are in line with the literature using the narrative approach, suggesting that the CAPB, when correctly specified, can be used as a measure of fiscal adjustments.
Keywords: E13; E22; E62; 330; fiscal policy; fiscal adjustment; narrative approach; cyclically adjusted primary balance